Viskositas dan Porositas Bahan Cetak Alginat dari Alga Merah Kappaphycus alvarezii - Rosi Endah Pratiwi; Izzata Barid; Didin Erma Indahyani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Alginate impression material is a material that is often used in dentistry to produce study models. The main active ingredient in the alginate impression material is sodium alginate, which can be obtained naturally from algae. Alginate from turbulent water (Waters on village Agel, Situbondo) and the structure of aliginate gluronic acid can form gel and influence the viscosity and the porosity of alginate impression material. Purpose was to analyze the viscosity and porosity of the alginate impression material from the red algae Kappaphycus alvarezii. This study is a laboratory experimental study with the research design of the post-test only control group design. This study consisted of 4 groups, namely the (1) viscosity control group, (2) porosity control, (3) viscosity treatment, and (4) porosity treatment. The porosity measurement results showed that there was no significant difference and the viscosity was significantly different from the control group because of the type of algae, the surface area of the particles, the preparation stage, the extraction that affected sodium alginate. Kappaphycus alvarezii type red alginate impression material has lower porosity than the standard Hygedent alginate impression material with a mean yield of 9%. The viscosity of the Kappaphycus alvarezii red alginate impression material based on the sigma standard is classified as high viscosity with an average of 33,200 cP.